Dementia of frontal lobe type and motor neuron disease. A Golgi study of the frontal cortex. Issue 10 (October 1991) - Ferrer, I; Roig, C; Espino, A; Peiro, G; Matias Guiu, X
Abstract : Neuropathological findings in a 38 year old patient with dementia of frontal lobe type and motor neuron disease included pyramidal tracts, myelin pallor and neuron loss, gliosis and chromatolysis in the hypoglossal nucleus, together with frontal atrophy, neuron loss, gliosis and spongiosis in the upper cortical layers of the frontal (and temporal) lobes. Most remaining pyramidal and non-pyramidal neurons (multipolar, bitufted and bipolar cells) in the upper layers (layers II and III) of the frontal cortex (area B) had reduced dendritic arbors, proximal dendritic varicosities and amputation of dendrites as revealed in optimally stained rapid Golgi sections. Pyramidal cells in these layers also showed depletion of dendritic spines. Neurons in the inner layers were preserved. Loss of receptive surfaces in neurons of the upper cortical layers in the frontal cortex are indicative of neuronal disconnection, and are "hidden" contributory morphological substrates for the development of dementia.